Določitev zaporedja montažnih operacij s hevrističnim sistemom HAP - Zorc, Samo (Strojniški vestnik, 2003)
The assembly-operation sequence-determination process is a part of the computer-aided assembly-planning system. Computer-aided assembly-sequence planning decisions are based on the product-assembly description and the relations between parts. The space relations between product parts are directly related to the movement geometry during the assembly process, and so for the assembly sequence determination a description of the space relation between the product parts can be used. The space of all possible assembly sequences is represented by an AND/OR graph. The graph is searched for the best sequence using a variant of the AO* heuristic algorithm. Assembly sequences are evaluated with respect to geometry feasibility, stability and modularity. To cope with the flexibility, efficient algorithms for generating and searching the problem space were developed and used. Empirical evaluations show the system can deal with read-world assemblies.
Keywords: planiranje montaže; zaporedja montaže; graf AND-OR; algoritmi heuristični; montaža; avtomatizacija; hevristični algoritmi